Forensic Investigation of the Steel Pile Pipe of the Mahakam Dolphin After Collision Using Side Scan Sonar and Bathymetry - Novia Safitri; Aco Wahyudi Efendi; Muh Yusuf; Irwan Faisal Luzan; Azan Zubran; Nova Amelia Putri; Amran (Civil Engineering Dept, Balikpapan State Polytechnics, 2026)
The Mahakam River in Samarinda, East Kalimantan, Indonesia, is a critical maritime transportation route with high vessel traffic, increasing the risk of collisions with bridge protection structures like dolphins. This study presents a forensic investigation into the position and shape of steel pile pipes of the Mahakam Dolphin after a collision incident, employing integrated bathymetric and side scan sonar surveys. Conducted in April 2026, the survey utilized Garmin ECHOMAP UHD2 62SV and GT52HW-TM transducers for bathymetry, alongside side scan sonar for high-resolution underwater imaging. Results revealed a compact debris field of collapsed steel pile pipes and pilecap, covering approximately 500 m² with an average thickness of 1.5 m. Bathymetric data indicated significant riverbed alterations, including scouring and sedimentation patterns. The debris distribution analysis confirmed minimal dispersion due to low current velocities, posing navigation risks and potential structural instability to adjacent bridge piers. The study underscores the efficacy of combined geophysical techniques in post-collision forensic assessments and recommends relocating the dolphin structure to a debris-free zone. These findings provide actionable insights for maritime infrastructure management and collision impact mitigation